STUDI ADSORPSI LOGAM Cu(II), Mn(II) DAN Ni(II) DALAM ARTIFICIAL LIMBAH CAIR DENGAN MENGGUNAKAN ADSORBEN NANOPARTIKEL MAGNETIT (Fe 3O4) - , Diah Mahmuda ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Magnetite nanoparticles (Fe3O4) have been successfully synthesized using coprecipitation method and used for removal metals ions Cu(II), Mn(II) and Ni(II) from artificial waste water. Ability of removing metal ions with Fe3O4 against temperature (RT, 60 , 90 and 120 ), adsorbent particle size (12 nm, 60 nm and 80 ), concentration of adsorbent (0.2 gr/L, 0.4 gr/L, 0.6 gr/L and 0.8 gr/L), reusing of adsorbent, re-adsorption and by addition of silica gel as coating agent of adsorbent have been studied. The adsorption process of Mn(II) and Ni(II) was found maximum at 120 with percent of sorption 63.07% for Mn(II) and 88,65% for Ni(II) while for Cu(II) was adsorbed 99.70% at room temperature. Concentrations and particles size also affected the metal sorption. Using 0.8 gr/L adsorbent, Cu(II) was adsorbed almost 99.85%. On the other hand, Mn(II) sorption was increasing along with decreasing of adsorbent particles size. From the experiments, it can be known that adsorbent Fe3O4 has a good stability because it can be used for repeatedly. Re-adsorption process and by addition of silica gel as coating agent of adsorbent also made the ability of removing metals ions increasing. Preliminary results indicate that magnetite nanoparticles may be used as an adsorbent for removal of Cu(II), Mn(II) and Ni(II) from wastewater